Hardware development of a UPQC in a power distribution system - Nyan, Paing Soe (2010)
The power electronic devices are extensively used in many practical applications over the past several years. This has raised the major problems of power quality in power distribution system. Voltage and current distortion as well as harmonic generation of the non linear load are typically found in the distributions system. These harmonic distortions are one of the main concerns in power quality for the power distribution system. In order to eliminate the harmonic distortion generated by non linear load and to compensate for voltage sag and swell in the power distribution system, Unified Power Quality Conditioner (UPQC) device is employed in the system. This report introduces the background phenomena and briefly states the scope of this project.